Pengaruh Kualitas Pelayanan terhadap Kepuasan Konsumen pada Toko Aneka Bakery and Cake Shop Panyabungan Mandailing Natal - Nur Khopipah; Andy Hakim; Muhlisah Lubis (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
This thesis discusses the influence of service quality on customer satisfaction at Aneka Bakery and Cake Shop. The purpose of this study is to determine the extent to which service quality affects customer satisfaction levels. The research employs a quantitative method with 97 respondents, determined using the Slovin formula with a 10% margin of error. Data were collected through questionnaires and analyzed using validity tests, reliability tests, normality tests, heteroscedasticity tests, partial tests (t-test), the coefficient of determination (R²), and simple linear regression analysis. The results indicate that service quality has a significant influence on customer satisfaction, as shown by a significance value of 0.00 < 0.05 and a t-count (23.525) > t-table (1.661). The coefficient of determination of 0.214 shows that 21.4% of the variation in customer satisfaction is influenced by service quality. The simple linear regression equation obtained is Y = 23.525 + 0.433X, meaning that every improvement in service quality will increase customer satisfaction at Aneka Bakery and Cake Shop.